2009
DOI: 10.1080/10509670802640925
|View full text |Cite
|
Sign up to set email alerts
|

Substance-Abusing Parents in the Criminal Justice System: Does Substance Abuse Treatment Improve Their Children's Outcomes?

Abstract: The expansion of the criminal justice system over the last several decades helped to focus attention on children of incarcerated parents, many of whom have parents with substance abuse problems. Since the 1990's, a national grassroots campaign has been underway to make substance abuse treatment an alternative to incarceration for parents who commit non-violent crimes. The question of interest in this article is what evidence there is, if any, that treating parental substance abuse changes children's outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
0
6
0
6
Order By: Relevance
“…One of the ''selling points'' of these programs is their purported benefits to children. Evaluation of such programs, however, typically focuses only on changes in parents' behaviors (e.g., changes in knowledge of parenting skills, substance use, and so forth) (Harm & Thompson, 1997;Palm, 2003;Spring, 1998) and, in some cases, on improvements in family conditions (e.g., reduced family conflict), some of which may have spill-over benefits for children (Phillips, Gleeson, & Waites-Garret, 2009). Notably missing from the evaluation of these programs are indicators of their effect on children's existing emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ''selling points'' of these programs is their purported benefits to children. Evaluation of such programs, however, typically focuses only on changes in parents' behaviors (e.g., changes in knowledge of parenting skills, substance use, and so forth) (Harm & Thompson, 1997;Palm, 2003;Spring, 1998) and, in some cases, on improvements in family conditions (e.g., reduced family conflict), some of which may have spill-over benefits for children (Phillips, Gleeson, & Waites-Garret, 2009). Notably missing from the evaluation of these programs are indicators of their effect on children's existing emotional and behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Of those participants committing such crimes, two-thirds had poor parental relationships and close to one-half described their families as not being close. Parental engagement and child-rearing practices, as well as parental substance use and incarceration, have been described as predictors of violent behavior in the literature (Phillips et al, 2009; Turner et al, 2007; Woldoff & Washington, 2008). A longitudinal, multiple cohort study of delinquency in boys from adolescence to young adulthood found that boys with four or more violence risk factors were six times more likely to commit violence and 14 times more likely to commit homicide as young adults than those with less than four risk factors (Loeber et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that may negatively influence the child-parent dynamic include parental substance abuse (Phillips et al, 2009; Woldoff & Washington, 2008). Parental risks increase a child’s exposure to poor living conditions, decrease access to education, and foster emotional and behavioral problems; these factors place the youth at risk for criminal behaviors, including violent criminality (Phillips et al, 2009; Turner et al, 2007). Results from this study provide further evidence that poor parental relations may negatively influence violent criminal activity into adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Father involvement is also related to children's outcomes. Children with involved, well-adjusted, resilient fathers who display warmth are significantly more likely to be emotionally stable and positive (Cuffe, McKeown, Addy, & Garrison, 2005), have healthy self-esteem, and exhibit empathy and pro-social behavior (Griffin, Botvin, Scheier, Diaz, & Miller, 2000;Phillips, Gleeson, & Waites Garrett, 2009).…”
Section: Fathermentioning
confidence: 99%